2020
DOI: 10.1039/d0ra03542d
|View full text |Cite
|
Sign up to set email alerts
|

The selection of highly specific and selective aptamers using modified SELEX and their use in process analytical techniques for Lucentis bioproduction

Abstract: Highly specific and selective aptamers for Lucentis were selected using 10 rounds of a modified and highly stringent SELEX process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The sequence of the ssDNA aptamer used for on-chip detection of Lucentis was (aptamer sequence 1 from our previous study on the selection of aptamers for Lucentis): 23 5′-AGGGAAGAGAAGGACATATGATGGGGGCTAGTATC-GACGTCTGCCTATGTTGTTAGTCGGTGTTGACTAGTACAT-GACCACTTG-3′.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence of the ssDNA aptamer used for on-chip detection of Lucentis was (aptamer sequence 1 from our previous study on the selection of aptamers for Lucentis): 23 5′-AGGGAAGAGAAGGACATATGATGGGGGCTAGTATC-GACGTCTGCCTATGTTGTTAGTCGGTGTTGACTAGTACAT-GACCACTTG-3′.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we reported the selection of specific aptamers for Lucentis using Systematic evolution of ligands by exponential enrichment (SELEX). 23 Additionally, an aptamer biosensor using non-faradaic impedimetric spectroscopy (NFIS) was fabricated to detect Lucentis in the fermenter for proof-of-concept. Major changes in the capacitive component of impedance were noticed in the biosensor upon complex formation between aptamer and Lucentis.…”
mentioning
confidence: 99%
“…Agarose beads have also been used as SELEX platforms and used to select aptamers for diverse chemicals [64][65][66]69,86]. Agarose beads are linear hydrogel polymers comprising repeated units of agarobiose.…”
Section: Bead-mediated Aptamer Selectionmentioning
confidence: 99%
“…The aptamer for Lucentis was selected by immobilizing the target on the agarose beads [ 66 ]. An aptamer with high affinity was obtained by decreasing the concentration of the immobilized target and the incubation time, increasing the number of washing steps, as well as expanding the elution procedure, which could reduce the number of cycles.…”
Section: Current Aptamer Discovery Strategies To Detect Chemicals and Biomoleculesmentioning
confidence: 99%
“…Aptamer sequences can bind with high specificity for their intended target, resulting in E-AB sensors with correspondingly high specificity and selectivity. [26][27][28][29][30] Why Focus on Electrochemical, Aptamer-Based Sensors?…”
mentioning
confidence: 99%